A theoretical framework for conflict resolution - El Fatih A. Abdel Salam (Universiti Kebangsaan Malaysia, 2001)
This study examines the parameters of ethnonational conflict theory. Ethnonational conflict is a widespread phenomenon. There have been many examples of such intrastate conflicts since the end of World War II. The reason for the focus on this type of conflict is that it is mostly waged in poor countries. Consequently, these conflicts tend to exacerbate the already abysmal poverty of these countries by destroying their fragile economic bases and inflicting endless misery upon generations of people. The study examines Micro as well as Macro theories of conflict. While the first emphasizes that the root causes of war lie in the human nature and human behaviour, the second focuses on the explicated, it is a fusion of developmental psychology and international relations theory and is used to explain terrorism in general. Human needs theory is human behaviour. Its basic assumption is that humans have basic needs that theory to practice by studying conflict resolution, track two diplomacy. This is an unofficial, informal interaction between members of adversary groups. This is in no way a substitute for official, formal, ‘track one’ government to government or leader – to leader relationships.